Comparison Of Outcomes Between Early And Delayed Reduction Of Nasal Bone Fractures - Amna Kousar; Sadia Chaudhry; Sundas Masood; Ansa Umara Akram; Amna Javaid; Adia Bushra Piracha (Journal of Rawalpindi Medical College)
Objective: To determine the outcomes of early versus delayed reduction of nasal bone fractures in terms of patient satisfaction and postoperative pain.